Refractory paroxysmal sympathetic hyperactivity following brain injury in a pregnant woman that dramatically improved after delivery. Issue 3 (8th December 2015) - Inoue, Akira; Ebina, Masatomo; Atsumi, Takahiro; Ariyoshi, Koichi
Abstract : Case: A 16‐year‐old primiparous girl in the 11th week of gestation presented to our hospital with a traumatic brain injury suffered during a motorcycle accident. She was comatose on arrival to the hospital and was admitted to the intensive care unit. From day 2, she developed intermittent episodes of tachycardia with tachypnea, fever, profuse sweating, and extensor posturing. She was diagnosed with paroxysmal sympathetic hyperactivity (PSH) and treated with morphine. However, paroxysmal sympathetic hyperactivity could not be controlled and her general condition deteriorated. Intrauterine fetal death was confirmed in the 16th week of gestation, on day 37 of hospitalization. P paroxysmal sympathetic hyperactivity increased each day until delivery and dramatically improved after delivery. Outcome: The patient gradually regained consciousness and was discharged to a rehabilitation hospital on day 117 after hospitalization. Conclusion: Pregnancy is a risk factor for paroxysmal sympathetic hyperactivity exacerbation, and delivery can result in resolution of the condition.